THE IMPORTANCE OF MARKETING COMMUNICATIONS IN TOURISM (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
This article presents opinions and comments about the tourism market, the importance of advertising, marketing communications, ways and methods of presenting tourism to the general public, the effects of using marketing strategies in tourism development, and the shortcomings that are being made.